The birth of modernism : Ezra Pound, T.S. Eliot, W.B. Yeats, and the occult - Surette, Leon (McGill-Queen's University Press, 1993)
In The Birth of Modernism Leon Surette offers a radical revision of our understanding of high modernism. Acknowledging that current post-modern and theoretical critiques have provoked fresh examination of the high culture of the first half of this century, Surette rejects their characterization of modernism as positivistic and absolutist, despite the statements in the 1920s of modernists such as Pound, Eliot, and Joyce. He also rejects the diametrically opposed New Critical view of modernism as sceptical and relativistic. Through an explanation of both familiar and little-known theoretical writings of the late nineteenth and early twentieth century -- the work of Friedrich Nietzsche receives particular attention -- Surette develops a portrait of modernism that demonstrates its continuity with American transcendentalism, French symbolisme, and English aestheticism. His account is, in many ways, a revival of an early view of modernism as the heir of symbolisme, but Surette documents, for the first time, the origins of modernist aesthetics in the occult. Yeats' occultism has long been acknowledged, but this is the first study to show that Pound's early intimacy with Yeats was based largely on a shared interest in the occult sciences, and that Pound's epic of the modern age, The Cantos, is a deeply occult work. To substantiate these claims Surette formulates a theory of the occult and analyses the occult speculations of several of Pound's close associates during his London years, relating these to the work of influential Continental occultists and Wagnerians. The author also examines the place of myth and mythopoeia in modernist literature. He scrutinizes the complex provenance of the theories of myth, to which modernists and their apologists appeal, and demonstrates that positive anthropology, Nietzschean philology, Wagnerian opera, symbolisme, and occultism all contribute to the theories expressed by Pound and, to some extent, to Eliot's poetry. In light of these discoveries Surette considers Pound's editing of Eliot's The Waste Land and concludes that the work's early reception as an expression of scepticism and relativism has obscured aspects of the poem that are consistent with Eliot's earlier and later piety. Pound's ruthless cutting of the manuscript, Surette asserts, was not motivated primarily by stylistic concerns, as has generally been contended in the formalist arguments of the New Critics, but by thematic considerations. It was precisely because Eliot knew Pound to be well-informed about the occult that he asked far his assistance with The Waste Land.